Who goes to school? : exploring exclusion in Indian education - Govinda, R.; Govinda, R.; Consortium for Research on Educational Access, Transitions & Equity; National University of Educational Planning and Administration (India) (New Delhi : Oxford University Press, 2011)
Contributed articles.
""Consortium for Research on Educational Access, Transitions & Equity ; National University of Educational Planning and Administration.""
Includes bibliographical references.
Keywords: Education, Primary -- India; Educational equalization -- India; Right to educatiopn -- India